Developments in the histories of sexualities : in search of the normal, 1600-1800 (Transits (Bucknell University), 2013)
The book develops and brings up to date the arguments about the history of sexuality first visited in Queer People: Negotiations and Expressions of Sexuality, 1600-1800 (Bucknell University Press, 2007). It marks a cautious farewell to Foucauldian analysis and begins to lay the groundwork for future methodologies for understandi.